2022
DOI: 10.1002/jid.3639
|View full text |Cite
|
Sign up to set email alerts
|

The potential for scaling up container‐based sanitation in informal settlements in Kenya

Abstract: Kenya has enshrined the right to sanitation in the 2010 constitution. Achieving this requires scaling up infrastructure and models of delivery beyond sewer networks that have previously been the focus. In Kenya, two enterprises, Sanergy and Sanivation, have been providing new forms of off‐grid services with container‐based sanitation (CBS). This paper uses a political economy analysis to understand the incentives, institutions and power dynamics that are enabling or constraining the potential for such off‐grid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…BSF larvae managed to reduce dried sisal decorticated waste by 52%, and dried fruit waste as the control was reduced by 78%. The obtained results in Table 7 show a positive correlation with previous studies, which indicates that waste reduction by BSF ranges from 58 to 70% [40], 53 to 80% [41,42], between 50 and 75%depending on the nature of the substrate [43]. Therefore, due to these findings, pre-treated sisal decorticated waste can be effectively managed using BSF, since the percentage reductions fall within the range being reported.…”
Section: Reduced Wastesupporting
confidence: 80%
“…BSF larvae managed to reduce dried sisal decorticated waste by 52%, and dried fruit waste as the control was reduced by 78%. The obtained results in Table 7 show a positive correlation with previous studies, which indicates that waste reduction by BSF ranges from 58 to 70% [40], 53 to 80% [41,42], between 50 and 75%depending on the nature of the substrate [43]. Therefore, due to these findings, pre-treated sisal decorticated waste can be effectively managed using BSF, since the percentage reductions fall within the range being reported.…”
Section: Reduced Wastesupporting
confidence: 80%
“…First, performance monitoring can take multiple forms and does not necessarily require an independent regulator. The literature commonly recommends approaches involving independent regulators as being most effective and transparent [3,5,8,13,17,115,128,129]. We observed this type of model in Abidjan and Cairo, where independent regulators tracked performance indicators and produced or reviewed annual reports covering multiple locations or utilities throughout the country [50,63].…”
Section: Overarching Lessons From the Three Types Of Progressmentioning
confidence: 91%
“…In our cases, these pro-poor measures appear to have been more important in making services more inclusive than constitutional rights to water. Existing literature has shown that explicit rights to water and sanitation, enshrined in national constitutions or other key policy documents, can sometimes be used in court cases to help improve access, although methods for their application may not always be clear [115,116]. In most of our cases, constitutional rights to water and sanitation did not exist.…”
Section: Governancementioning
confidence: 94%
See 1 more Smart Citation
“…There is limited evidence of cost recovery from waste to resource schemes to date. A recent review identified that few cases were able to achieve more than $5/person/year from sludge reuse (Mallory et al, 2020) and other resource recovery schemes within Kenya are reliant on government investment to be viable (Mallory et al, 2022). However, to dismiss it as an opportunity would be short sighted.…”
Section: Resourcing Sanitation At a Citywide Scale Financing Going...mentioning
confidence: 99%